Why Politicians Favor Redheads - A Theory of Tactical Horizontal Redistribution. - Sören Blomquist; Vidar Christiansen (Uppsala University, Department of Economics, 2000)
This paper studies a very pure form of vote purchasing. We consider whether it may be in the interest of a party to discriminate between groups that, possibly except for size, are identical in all welfare relevant spects, i.e. the groups are assumed to have the same income, needs, etc. To emphasise this aspect we label the groups brown-heads and redheads. The interpretation is that they differ only in some characteristic that is entirely irrelevant from a welfare perspective. There are no systematic differences between people with the same income. Taking two samples of people from an income class their political support will be identically distributed. We will show that even with these uniformity assumptions there can be strong incentives for political parties to undertake vote purchasing by favouring one of the identical groups at the expense of the other.
Keywords: D72; 330; vote purchasing; tactical redistribution; political economy; Wahl; Ökonomische Theorie der Demokratie; Neue politische Ökonomie; Theorie